2015
DOI: 10.3390/molecules21010019
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanide-Based Multicomponent Reactions for the Synthesis of Heterocycles

Abstract: Multicomponent reactions (MCRs) are extremely popular owing to their facile execution, high atom-efficiency and the high diversity of products. MCRs can be used to access various heterocycles and highly functionalized scaffolds, and thus have been invaluable tools in total synthesis, drug discovery and bioconjugation. Traditional isocyanide-based MCRs utilize an external nucleophile attacking the reactive nitrilium ion, the key intermediate formed in the reaction of the imine and the isocyanide. However, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 81 publications
0
57
0
3
Order By: Relevance
“…S3 ESI †). [26][27][28][29][30][31] However, the impact of this generated chiral center on the final product is minimized by the fact that it will be removed during the backbone amide deprotection step (Scheme 2). Moreover, the presence of only two diastereomers confirmed that the peptide's stereochemistry is conserved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 ESI †). [26][27][28][29][30][31] However, the impact of this generated chiral center on the final product is minimized by the fact that it will be removed during the backbone amide deprotection step (Scheme 2). Moreover, the presence of only two diastereomers confirmed that the peptide's stereochemistry is conserved.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the Ugi four-component reaction (Ugi-4CR) is very attractive as it offers a great inputs diversity to access complex molecules with high efficiency and atom economy. [26][27][28][29][30][31] The Ugi-4CR involves the reaction of isocyanide, carboxylic acid, amine and carbonyl compounds to afford a α-acylamino amide. 30,31 As the generated tertiary amide bond is formed between the amine and the acid components, the Ugi-4CR has been successfully used in the preparation of linear and macrocyclic peptides.…”
Section: Introductionmentioning
confidence: 99%
“…MCRs have been also applied in polymer [74], nucleoside [75] and carbohydrate [76] chemistry. Main field of application remains the production of heterocyclic compounds and many natural products by means of MCR [38,[77][78][79][80][81][82][83][84][85][86][87][88][89], leading directly towards drug design and discovery [90][91][92][93][94]. Scheme 9 presents a current brief of well-known multicomponent reactions [35,40,9,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Methodsmentioning
confidence: 99%
“…The field of peptidomimetics has seen an exciting development over the past several years, partly due to the considerable biological importance and putative proteolytic stability of synthetic peptoids over native peptides [1][2][3]. Recently, Ugi coupling [4][5][6][7][8] of various carboxylic acids, amines, isocyanates and aldehydes to a series of tripeptoids has been found to give excellent yields and these have also been reported to exhibit antifungal and antimicrobial activities [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%